2021
DOI: 10.1186/s40779-021-00327-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydration status, body composition, and anxiety status in aeronautical military personnel from Spain: a cross-sectional study

Abstract: Background An adequate hydration status is critical to ensure efficiency during mental and physical activities. Our goal was to assess the hydration status of a Spanish group of aeronautical military men and to determine the association of hydration status with body composition and anxiety. Methods A total of 188 men were evaluated through a validated hydration questionnaire, anthropometric and biochemical parameters, and an anxiety questionnaire. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Characteristics of the included studies are shown in Tables 1 and 2. Of the 105 included studies, 81 studies 20,23,25,26,28–30,32,34–46,48–56,58–65,67–71,74–76,78–84,86–92,95–99,101,103,104,106,109,113,115–124 were classified as studies primarily designed to measure fluid intake (intervention or observational studies), and 24 18,19,21,22,24,27,31,33,47,57,66,73,77,85,94,100,102,105,107,108,110–112,114 studies were classified as methodological studies evaluating accuracy and/or reliability of dietary assessment tools.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the included studies are shown in Tables 1 and 2. Of the 105 included studies, 81 studies 20,23,25,26,28–30,32,34–46,48–56,58–65,67–71,74–76,78–84,86–92,95–99,101,103,104,106,109,113,115–124 were classified as studies primarily designed to measure fluid intake (intervention or observational studies), and 24 18,19,21,22,24,27,31,33,47,57,66,73,77,85,94,100,102,105,107,108,110–112,114 studies were classified as methodological studies evaluating accuracy and/or reliability of dietary assessment tools.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the probability of discharge from the military increases [ 5 ]. Carretero-Krug et al reported that inadequate hydration during exercise increases anxiety and that palpitations negatively affect mental performance [ 6 ]. Heat strokes are common in the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had revealed that there was certain positive degree of association between water intake and body water content [23][24][25][26]. Indeed, individuals with different levels of water intake had differed hydration biomarkers including the urine osmolality, urine speci c gravity (USG), among young adults and athletes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%